2003
DOI: 10.1021/ol035878k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Regioselective Arylation of Imidazo[1,2-a]pyrimidine

Abstract: Imidazo[1,2-a]pyrimidine can be arylated at the 3-position with aryl bromides in the presence of base and a catalytic amount of palladium. This provides an efficient one-step synthesis of 3-arylimidazo[1,2-a]pyrimidines from the unsubstituted heterocycle. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 15 publications
2
50
0
1
Order By: Relevance
“…A method for direct arylation and heteroarylation of imidazopyrimidine 66 was reported by Li (Scheme 28). 43 The protocol involved employment of the Pd(OAc) 2 /PPh 3 catalytic system in the presence of Cs 2 CO 3 in dioxane, affording the corresponding aryl derivatives 67 with good to excellent yields (Scheme 28). 43 It was suggested that this arylation proceeds via Miura's electrophilic mechanism.…”
Section: Reactions Involving Pd 0 /Pd II Manifold: Synthetic Applicatmentioning
confidence: 99%
See 2 more Smart Citations
“…A method for direct arylation and heteroarylation of imidazopyrimidine 66 was reported by Li (Scheme 28). 43 The protocol involved employment of the Pd(OAc) 2 /PPh 3 catalytic system in the presence of Cs 2 CO 3 in dioxane, affording the corresponding aryl derivatives 67 with good to excellent yields (Scheme 28). 43 It was suggested that this arylation proceeds via Miura's electrophilic mechanism.…”
Section: Reactions Involving Pd 0 /Pd II Manifold: Synthetic Applicatmentioning
confidence: 99%
“…43 The protocol involved employment of the Pd(OAc) 2 /PPh 3 catalytic system in the presence of Cs 2 CO 3 in dioxane, affording the corresponding aryl derivatives 67 with good to excellent yields (Scheme 28). 43 It was suggested that this arylation proceeds via Miura's electrophilic mechanism. 3 Gevorgyan reported an efficient and regioselective method for C-3 arylation and heteroarylation of indolizines 68 (Scheme 29).…”
Section: Reactions Involving Pd 0 /Pd II Manifold: Synthetic Applicatmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The reaction has been employed as a key step in the synthesis of a potential GABA agonist drug candidate, 2 0 ,4-difluoro-5 0 -(7-trifluoromethylimidazo[1,2-a]pyrimidin-3-yl)biphenyl-2-carbonitrile. The arylation of oxazolo [4,5-b]pyridine can be carried out under mild conditions (Scheme 26).…”
mentioning
confidence: 99%
“…The pK a values were determined by analysing the UV chromophores during a pH titration (using Sirius SGA technology) and, for the compounds 7 and 9, the values obtained are very close to those previously published in the literature. 20,21 Interestingly, in both the unsubstituted and 7-isopropanol series, it is clear that the C-F unit (in 11 and 12) alters the pK a in an identical manner to an azine nitrogen (in 9 and 10), that is, by approximately two units. Log D 7.4 values were determined using the traditional 'shake-flask' method with partitioning between octanol and a pH 7.4 buffer.…”
mentioning
confidence: 99%